Politics of despotic leaders: subversion, repression and development in the Hazara Ismaili Community of Afghanistan - Emadi, Hafizullah (Peter Lang, 2024)
The book demonstrates the prominent role the local religious leaders played in the lives of the Ismaili community and the governance strategies they adopted to portray themselves as demi-god forcing people to develop blind faith in them, submit to their leadership and follow their dictates unquestioned